Building capacities for peace-positive climate adaptation: lessons from Kenya’s County Climate Change Fund - Medina, Leonardo; Osumba, Joab; Takaindisa, Joyce; Mukutu, Munini; Schapendonk, Frans; Jaskolski, Martina; Ndwiga, Murugi (2026)
Climate adaptation in conflict-affected settings can unintentionally exacerbate existing tensions if social and political dynamics are not adequately addressed. This policy brief examines how institutional capacity development can support peace-positive climate adaptation in Kenya’s arid and semi-arid lands, drawing on an in-depth assessment of the County Climate Change Fund (CCCF). Based on a mixed-methods analysis combining policy review, participatory needs assessments, community surveys, and a multi-stakeholder workshop, the brief explores how devolved governance shapes both opportunities and constraints for integrating conflict sensitivity into climate action. The findings highlight the importance of situating capacity building efforts in de-facto institutional practices, leveraging existing participatory governance mechanisms, and treating cross-sectoral integration between climate adaptation and peacebuilding as a process of social and institutional learning, rather than a technical fix. The brief concludes with practical recommendations to strengthen conflict analysis, coordination, early warning systems, and accountability within the CCCF, offering transferable lessons for capacity development in other devolved and conflict-prone contexts.